Midwifery leadership, advocacy and action to improve maternal health in PNG. (30th September 2020) - Hall, H; Kep, J; Brown, J; Pyakalyia, J; King, R; Mahmood, A; Sitaing, M
Abstract: Background: The SDG target for maternal mortality is less than 70 per 100, 000 live births; in Papua New Guinea, it is estimated to be 145. PNG will require significant resources and strong leadership to meet the 2030 target. The PNG Midwifery Leadership Buddy Program (Buddy Program), funded and coordinated by Rotary, offers an innovative model to improve maternal health, which may be transferable to other low-middle-income countries. Objectives: The Buddy Program aims to build midwifery leadership resulting in improved outcomes in PNG. As partners, midwives from PNG and Australia undertake leadership training in Port Moresby and enter a reciprocal peer support relationship. Over 12 months, they support each other in their professional roles and progress a quality improvement project. Results: Three cohorts of midwives (18 from each country), have participated in the leadership training and the first group has completed 12 months of peer support. Participants have reported increased confidence for leadership, action and advocacy. There has been some communication challenges and variation in expectations, predominately due to cultural differences. The Buddy Program has resulted in a number of tangible projects including the introduction of family planning education at a local school and University, introduction of respectful care in pregnancy charter and increased surveillance and treatment of pregnant women with anaemia. Interestingly, a number of participants have continued to support each other beyond the initial 12-month commitment. Conclusions: Supportive partnerships that grow midwifery leadership hold significant potential to increase the quality of maternity care and reduce preventable maternal deaths in low-middle-income countries. Key messages: Midwifery leadership plays a vital role in addressing the SDG targets for maternal health. The Buddy Program offers an innovative model to progress the agenda for universal access to quality maternity care.